(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to examine the relationship between future time perception and career anxiety levels of individuals who participated in the special talent examination and to evaluate their future time perception and career anxiety scores according to independent variables. The sample of the research consists of 178 people selected by simple random sampling method among the individuals who participated in the special talent examination. The research was designed according to the relational screening model. Sociodemographic information form, future time perception scale and career anxiety scale were used as data collection tools. Findings from the research; future time perception and general career anxiety average scores do not differ according to gender. Vocational choice and general career anxiety scores of the participants over the age of 18 are higher than those under the age of 18. The career anxiety family effect average score of the participants with a university basic proficiency exam score below 191 points is higher than those with a score above 191 points. There is a statistically low, and negative correlation between the commitment sub-dimension of the future time perception scale and the general career anxiety score.